2021
DOI: 10.7150/thno.62376
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-dependent neuronal necroptosis regulated in Alzheimer's disease by coordination of RIPK1-p62 complex with autophagic UVRAG

Abstract: Background: Neuronal death is a major hallmark of Alzheimer's disease (AD). Necroptosis, as a programmed necrotic process, is activated in AD. However, what signals and factors initiate necroptosis in AD is largely unknown. Methods: We examined the expression levels of critical molecules in necroptotic signaling pathway by immunohistochemistry (IHC) staining and immunoblotting using brain tissues from AD patients and AD mouse models of APP/PS1 and 5×FAD. We performed brain st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 65 publications
3
67
0
Order By: Relevance
“…Neuronal loss in AD is due to TNF-mediated necroptosis rather than apoptosis [ 46 ]. Accumulating evidence shows an important link between TNF and AD, and the TNF- α signaling pathway predominantly mediates inflammatory and proapoptotic signaling pathways [ 47 ]. In addition, TNF is involved in systemic inflammation; TNF and TNF receptor type 1 participate in neuroinflammation associated with AD and are also involved in amyloid- β formation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal loss in AD is due to TNF-mediated necroptosis rather than apoptosis [ 46 ]. Accumulating evidence shows an important link between TNF and AD, and the TNF- α signaling pathway predominantly mediates inflammatory and proapoptotic signaling pathways [ 47 ]. In addition, TNF is involved in systemic inflammation; TNF and TNF receptor type 1 participate in neuroinflammation associated with AD and are also involved in amyloid- β formation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that overactivated M1 phenotype microglia can cause neuronal disability, damage and degeneration; and play an important role in cerebrovascular and neurodegenerative diseases and neurodevelopmental and mental disorders [ 16 , 45 , 46 , 47 ]. Microglia secrete proinflammatory factors including Interleukin-1β [ 26 , 27 , 48 , 49 ], Interleukin-6 [ 49 , 50 , 51 ] and TNFα [ 49 , 52 , 53 ], along with an increased production of ROS [ 54 , 55 , 56 ], which can cause damage to the surrounding neuronal cells. In AD, M1 phenotype microglia that secrete pro-inflammatory factors maintain the neuroinflammatory microenvironment and continuously aggravate neuronal damage.…”
Section: Metabolic Reprogramming Of Microglia To Aggravate the Neuroi...mentioning
confidence: 99%
“…RIPK3 and MLKL are important for necroptosis activation [58,[152][153][154][155]158,165,166]. TNF-α/TNFR1-induced necroptosis occurs in several neurodegenerative diseases of the CNS, such as multiple sclerosis (MS), Parkinson's disease and Alzheimer's disease [156,[167][168][169][170]. After an ischaemic stroke, perivascular microglia-induced endothelial necroptosis leading to disruption of the bloodbrain barrier requires TNF-α to act on its receptor TNFR1 [57].…”
Section: Tnf-α/tnfr1-necroptosis Pathway Contributes To Neurological ...mentioning
confidence: 99%